Pedestrian behavioural intention to use crossing facilities based on extended theory of planned behavior - Komala Devi Sundararajan; Kamarudin Ambak; Basil David Daniel; Siti Zaharah Ishak; Putranto, Leksmono Suryo (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Malaysia, pedestrian has become a regulartransportation mode with major importance in human society.For pedestrians to cross the busy main road, crossing facilities is perhaps the most crucial. It is most important to establish a way of preventing a tragedy and to make the pedestrian aware of the need to perform a safety crossing in order to prevent an accident. The objectives of study are to investigate the contributing factors that affect pedestrians to use a crossing facility and to analyse the relationship between the contributing factors and a safe crossing behaviour. In this analysis, Theory of Planned Behaviour (TPB) was used to explain this outcome and decide whether characteristics and attitude influence the pedestrian’s behaviour involved in the accident. For the purpose of gathering information from the respondents, a questionnaire was used as a research tool which consists a series of questions and other prompts. The collected data were analysed using descriptive statistics, correlation, factor analysis and Structural Equation Model (SEM). Results show all variables are significantly contributed to safe crossing behavior. There are two most dominant variables namely perceived consequence and expectation of pedestrian toward safe crossing behavior. TPB model is therefore capable of explaining the significant factors influencing the pedestrian’s intention to safe crossing behaviour. The most dominant variable of the extended model of TPB is expectation. Pedestrian’s expectation is high toward proper crossing facility, authorities should intervene with the design infrastructure to attract more pedestrians to use the crossing and there is a need to provide sufficient signal time for pedestrians to cross the street safely.